Investigations on Sarcocystis species in the leg muscles of the bird family Corvidae in Lithuania - Juozaitytė-Ngugu, Evelina; Butkauskas, Dalius; Švažas, Saulius; Prakas, Petras (Parasitology research (1987), 2022)
Although three species of Sarcocystis , S . cornixi , S . corvusi and S . kutkienae , have been described in corvids, molecular studies of sarcocysts isolated from these birds are incomplete. Leg muscles of 83 corvids, 35 hooded crows ( Corvus cornix ), 21 western jackdaws ( Coloeus monedula ), 11 rooks ( Corvus frugilegus ), 9 common ravens ( Corvus corax ), 4 common magpies ( Pica pica ) and 3 Eurasian jays ( Garrulus glandarius ), from Lithuania were examined for the presence of Sarcocystis spp. in the present study. In methylene blue–stained squashed samples, sarcocysts were detected in 26 birds (31.0%). Under a light microscope, two morphological types of sarcocysts were distinguished (type A and type B). Sarcocysts of type A had a smooth and thin (about 1 μm) cyst wall, while cysts of type B were characterised by a thicker (1.4–2.5 μm) cyst wall. Based on ITS1 sequence comparison, sarcocysts of type A were identified as S . halieti and Sarcocystis sp. ex Corvus corax , whereas cysts of type B belonged to S . kutkienae and S . cornixi . Furthermore, it was demonstrated that a single bird could host two different Sarcocystis spp. Sarcocystis halieti was detected in corvids for the first time in the common raven and the hooded crow. Also, this study presents the first evidence of S . kutkienae in the hooded crow and the common magpie, and S . cornixi in the western jackdaw. Sarcocystis sp. ex Corvus corax was genetically characterised using almost complete 18S rDNA, partial 28S rDNA and complete ITS1 sequences. Sarcocystis sp. ex Corvus corax clustered together with S . columbae , S . corvusi and S . halieti in phylogenetic trees reconstructed using 28S rDNA and ITS1 sequences.